(untitled) - Graham, Billy; (1918-2018) (USA, 2015)
While his earthly vision dims, the glory of Heaven illumines as beloved evangelist Billy Graham, shares from his past, and present, the reality of eternity in Where I Am. Although Mr. Graham no longer preaches from the stadiums of the world, you will sense his heart still beats strong with the resounding assurance that he will spend eternity with Jesus Christ, the Savior of the world, as he invites others to contemplate their eternal hope
Keywords: Future life Biblical teaching